In search of biomarkers for low back pain: can traction therapy effectiveness be prognosed by surface electromyography or blood parameters? - Ratajczak, Marzena; Waszak, Małgorzata; Śliwicka, Ewa; Wendt, Michał; Skrypnik, Damian; Zieliński, Jacek; Krutki, Piotr (Frontiers in Physiology, 2023)
Background: Lumbar traction therapy is a common method to reduce low back pain (LBP) but is not always effective. The search for biomarkers that would prognose the effectiveness of LBP management is one priority for improving patients' quality of life.(1) To determine the phenotype of patients benefiting most from lumbar traction therapy. (2) To correlate systemic and electromyographic biomarkers with pain and pain-related disability.Methods: Data on muscle bioelectrical activity (surface electromyography [SEMG]) in the flexionextension task, the concentrations of twelve systemic biochemical factors, LBP intensity (Visual Analog Scale), the Oswestry Disability Index, and the Roland-Morris Disability Questionnaire (RMDQ) were collected before and 72 h after 20 sessions of lumbar traction therapy. Patients were divided into responders and nonresponders based on the criterion of a 50% reduction in maximal pain.The responders had lower maximal muscle bioactivity in the extension phase on the left side (p<0.01) and higher flexion-extension ratios on both sides of the body in the SEMG (left: p<0.05; right: p<0.01), and higher adipsin, interleukin-2, interleukin-4, and interleukin-10 concentrations (p<0.05) than nonresponders. Patients with higher interleukin-4 concentrations before therapy achieved greater reductions in maximal pain in the sitting position, bioelectrical muscle activity in flexion, and flexion-relaxation ratio on the left side of the body. Changes in adipsin and interleukin-4 concentrations correlated with changes in LBP intensity (r=0.68; r=-0.77).Changes in stem cell growth factor and interleukin-17A correlated with changes in RMDQ (R=0.53) and bioelectrical muscle activity in extension (left: R=-0.67; right: R=-0.76), respectively.Conclusions: Responders to traction therapy had SEMG indices of less favorable muscle activity in the flexion-extension task and elevated indices of inflammation before the study. For the first time, interleukin-4 was indicated as a potential biomarker for prognosing post-therapy changes in pain intensity and muscle activity.